Estandarización de protocolo de cultivo primario de Cardiomiocitos de ratas neonatas aplicando la Norma ISO 9001:2015 – Chile 2019 - Anticona Salazar, Enrique Junior (2020)
The present report entitled STANDARDIZATION OF PRIMARY CULTURE PROTOCOL OF NEONATE RAT CARDIOMYOCYTES APPLYING - ISO 9001:2015 - CHILE 2019, has as main objective to standardize a protocol of primary culture of neonatal rat cardiomyocytes applying, which is used as a previous procedure for conducting the experiments. That is why it was decided to follow the basic steps, based on the standardization of procedures through the ISO 9001:2015 standard. To carry out the standardization, the first thing that was done was to look for the information of the existing methodology, with which it was found that the laboratory had a written procedure. This was followed by testing the protocol used for primary culture of existing neonatal rat cardiomyocytes. Subsequently, weaknesses were identified, in order to generate observations of improvement of the primary culture protocol of neonatal rat cardiomyocytes. Where they highlighted, latent risk of cell culture contamination (laminar flow hood hygiene), poor specimen asepsis, poor specimen handling, handling of culture media Then a first draft of the primary culture protocol of neonatal rat cardiomyocytes was tested, where it was observed if the recommendations made were useful, then final recommendations were generated that should be taken into account during the implementation of the protocol, and finally a document was made of the standardized protocol for obtaining primary culture of neonatal rats cardiomyocytes, following general guidelines of the ISO 9001:2015 standard